2019
DOI: 10.1136/esmoopen-2019-000498
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitor treatment in patients with oncogene-addicted non-small cell lung cancer (NSCLC): summary of a multidisciplinary round-table discussion

Abstract: The introduction of targeted treatments and more recently immune checkpoint inhibitors (ICI) to the treatment of metastatic non-small cell lung cancer (NSCLC) has dramatically changed the prognosis of selected patients. For patients with oncogene-addicted metastatic NSCLC harbouring an epidermal growth factor receptor (EGFR) or v-Raf murine sarcoma viral oncogene homologue B1 (BRAF) mutation or an anaplastic lymphoma kinase (ALK) or ROS proto-oncogene 1, receptor tyrosine kinase (ROS1) gene alteration (translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 79 publications
(106 reference statements)
2
39
0
Order By: Relevance
“…Berghoff et al recently reviewed ICI treatment in patients with oncogene-addicted NSCLC (Berghoff et al 2019). They evaluated the efficacy of ICIs in NSCLC patients with wild-type EGFR and in patients with EGFR-mutated NSCLC in five clinical trials: CheckMate 057 (Borghaei et al 2015), KEYNOTE-010 (Herbst et al 2016), OAK (Rittmeyer et al 2017), POPLAR (Fehrenbacher et al 2016), and IMpower150 (Socinski et al 2018), and found that the survival benefits of treatment with an ICI tended to and December 2018, the 263 patients were adopted as the subjects of this study and divided into 4 groups based on their programmed death-ligand-1 (PD-L1) expression level and EGFR mutation status.…”
Section: Discussionmentioning
confidence: 99%
“…Berghoff et al recently reviewed ICI treatment in patients with oncogene-addicted NSCLC (Berghoff et al 2019). They evaluated the efficacy of ICIs in NSCLC patients with wild-type EGFR and in patients with EGFR-mutated NSCLC in five clinical trials: CheckMate 057 (Borghaei et al 2015), KEYNOTE-010 (Herbst et al 2016), OAK (Rittmeyer et al 2017), POPLAR (Fehrenbacher et al 2016), and IMpower150 (Socinski et al 2018), and found that the survival benefits of treatment with an ICI tended to and December 2018, the 263 patients were adopted as the subjects of this study and divided into 4 groups based on their programmed death-ligand-1 (PD-L1) expression level and EGFR mutation status.…”
Section: Discussionmentioning
confidence: 99%
“…3,48 Conversely, tumours with oncogene addiction such as non-small cell lung cancer with ALK fusion or EGFR mutation have been shown to have lower TMB and lower likelihood of response to ICI in lung cancer. 61,62 While these findings require validation across tumour types and contexts, they raise the question of whether tumours with a single gene driver -such as iCCA with FGFR2 fusions -may harbour fewer tumour-associated antigens and consequently have lower response rates to ICI. Future subanalyses of ICI studies in CCA, according to tumour mutational status, are needed to confirm whether certain genetically defined subgroups are more or less likely to respond to ICI.…”
Section: Tumour Geneticsmentioning
confidence: 99%
“…Despite promising advances in immunotherapy, the role of ICIs in oncogene-addicted NSCLC remains unclear and conflicting. The majority of data come from subgroup analyses with low number of patients, therefore the use of ICIs, when permitted by regulatory agencies, should only be considered when other available therapies, including standard EGFR-TKIs, fail (34).…”
Section: Immunotherapy In the Management Of Egfr-mutated Lung Cancermentioning
confidence: 99%